Effect of Oxygen and Temperature on the Efficiency of Photosynthetic Carbon Assimilation in Two Microscopic Algae - Coleman, John R. (1980)
The CO(2) compensation points of Coccochloris peniocystis, a blue-green alga and Chlamydomonas reinhardtii, a green alga, were determined at pH 8.0 in a closed system by a gas chromatographic technique. The compensation point of Chlamydomonas increased markedly with temperature, rising from 0.79 microliter per liter CO(2) at 15 C to 2.5 microliters per liter CO(2) at 35 C. In contrast, the compensation point of Coccochloris at 20 C was 0.71 microliter per liter CO(2) and rose to only 0.95 microliter per liter CO(2) at 40 C. The compensation point of the green alga was significantly reduced at low O(2) concentrations (1 to 2%) when measured over the temperature range of 15 to 35 C. The compensation point of the blue-green alga, over the temperature range of 20 to 40 C, was unaffected by lowering the O(2) concentration. The whole cell CO(2) affinity of Chlamydomonas decreased substantially with increasing temperature at 21% O(2) whereas little change was observed over the same temperature regime when the CO(2) affinity was determined at O(2) concentrations of 1 to 2%. The CO(2) affinity of Coccochloris did not decrease significantly with either increasing temperature or O(2) concentration. These results suggest that while photorespiration is undetectable in Coccochloris some photorespiratory CO(2) release occurs in Chlamydomonas.